Comparing the physical activity of stroke survivors in high‐income countries and low to middle‐income countries. - Jayawardana, Krishni S.; Crowfoot, Gary; Janssen, Heidi; Nayak, Pradeepa; Solomon, John M.; English, Coralie K. (Physiotherapy Research International, 2021)
Background: Low physical activity levels in people with stroke may contribute to higher risk of cardiovascular disease morbidity and mortality. Differences in economic status, culture and the built environment may influence the applicability of interventions developed in high income countries (HIC) for stroke survivors in low to middle‐income countries (LMIC). Purpose: To compare physical activity levels of stroke survivors in HIC and LMIC and to explore the influence of lower limb impairment on physical activity levels. Methods and Materials: An exploratory secondary analysis of observational data on physical activity levels of stroke survivors from Australia (HIC) and India (LMIC). Physical activity variables (step count, light physical activity (LPA) and moderate‐to‐vigorous physical activity (MVPA)) were measured by accelerometery. Comparisons of physical activity levels between (a) Australian and Indian stroke survivors and (b) participants with and without lower limb impairments were performed using independent t‐tests or Mann‐Whitney U tests. Results: There were no significant differences in physical activity levels between (i) Australian and Indian stroke survivors (step count mean difference 201 steps [−1375 to 974], LPA mean difference −24 min [−22 to 69], MVPA mean difference 2 min [−8 to 3]), and (ii) stroke survivors with and without lower limb impairments in either country. Conclusion: Stroke survivors were highly inactive in both countries. Despite differences in economic status, cultural influences and the built environment, the physical activity of stroke survivors in Australia and India did not differ. People with and without lower limb impairment also had similar physical activity levels.